Estimation of acoustic indices with CVs for cod and haddock in the Barents Sea winter survey 1994 – 2017 applying the Sea2Data StoX software - Mehl, Sigbjørn; Aglen, Asgeir; Johnsen, Espen; Skålevik, Åsmund (Havforskningsinstituttet, 2018)
Source at https://www.hi.no/publikasjoner/andre_publikasjoner/fisken_og_havet/2018/nb-no . English : The Sea2Data software StoX was applied to estimate acoustic indices with CVs for Northeast Arctic cod and haddock from the Barents Sea winter survey in 1994 to 2017. The indices are compared to indices previously estimated by the BEAM software. In most years the StoX indices for cod are quite similar to those obtained by BEAM, while they are somewhat higher for haddock. The largest deviations were mainly found for age groups with low indices and/or in years with raising of the indices. Norwegian : Sea2Data programmet StoX er brukt til å estimere akustiske indekser med CV for nordøstarktisk torsk og hyse fra vintertoktet i Barentshavet i 1994 til 2017. Indeksene er sammenlignet med indekser tidligere estimert med programmet BEAM. I de fleste år er StoX indeksene for torsk nokså like BEAM indeksene, mens de er noe høyere for hyse. De største forskjellene var hovedsakelig for aldersgrupper med lave indekser og/eller i år med skalering av indeksene.